Additional Employee Income Policy at the Personnel and Human Resources Development Agency of Barru Regency - Khusnul Hatimah; Nurfitraeny Nasruddin; Dewi Dewi (ASHA Publishing, 2025)
The performance of state civil servants is a fundamental pillar in the effective and efficient delivery of public services. In an effort to improve both employee performance and welfare, the Barru Regency Government implemented the Additional Employee Income (TPP) policy. This research aims to identify the implementation of the TPP policy in relation to improving employee performance at the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Barru Regency. This research uses a qualitative method with a descriptive approach. Data collection was carried out through a combination of in-depth interviews with agency leaders, direct observation of work activities and discipline, and documentation studies covering employee attendance and daily reports. The collected data was analyzed for validity using triangulation techniques. The results show that the determination of the TPP amount at the BKPSDM of Barru Regency is based on five integrated criteria: position, rank/class, educational background, level of discipline, and performance achievement. Field findings confirm that the level of employee discipline, measured by adherence to working hours and attendance at roll calls (apel), is in the very good category. Employee performance, evidenced by the timeliness and completeness of daily reports and the completion of main and additional tasks, also shows good results. In conclusion, the TPP policy at BKPSDM Barru has created a mechanism that directly links additional compensation with individual contributions. The high level of employee discipline and performance is the basis for the proportional justification of TPP provision, which serves as an incentive instrument to encourage work productivity.